Decree No. 279 of the Year 2025 - Ministry Of Environment (The Middle East Library For Economic Services, 2025)
Following the reviewal of Law Regulating the Management of Waste, promulgated by law no. 202 of the year 2020, its executive regulations and their amendments Decree of the Minister of Environment no. 113 of the year 2022, Concerning the determination of the categories and fees for the issuance of licenses, approvals, and permits for integrated management activities of hazardous and non-hazardous materials and waste by the Waste Management Regulatory Authority Article: 1 In addition to the prescribed value-added tax (VAT), the fees for the following services provided by the Waste Management Regulatory Authority shall be determined as follows: 1- A fee of EGP 2,000 (two thousand Egyptian pounds only) shall be collected against reviewing the applications for introducing any amendments to licenses, approvals, or permits issued by the Waste Management Regulatory Authority for integrated management activities of hazardous and non-hazardous materials and waste. 2- A fee of EGP 2,000 (two thousand Egyptian pounds only) shall be collected for filing a grievance against the decisions arising from the application of the provisions of the Waste Management Law No. 202 of the year 2020.